The twin faces of pleasure: The relationship between pleasure and compassion fatigue (Frontiers in Psychology, 2015)
Aims: Compassion Fatigue (CF) can be pervasive and debilitating for individuals in some professions. For organisations, it can result in substantial costs in terms of staff productivity and retention. Activities found to be pleasurable - termed hedonic - may play a protective role during times of stress. However, hedonic activities can also be used in ways that are risky and maladaptive. Two theories were tested in the current study: firstly, that hedonic pleasure is used adaptively to counteract factors that may lead to CF; and secondly, that hedonic pursuits are used maladaptively and thus represent risk factors for CF. Method: 176 adults (74% female) completed a suite of questionnaires presented online. Two self-report scales assessed the individual's behaviour related to pleasurable activities. The TEPS captured behaviour of an adaptive nature, while the ‘shorter PROMIS’ measured maladaptive uses of pleasure. Compassion Fatigue was assessed with a sub-scale of the Professional Quality of Life scale (ProQOL).